Człowiek i rodzina w XXI wieku. Czas nadziei czy cywilizacja udrąki? - Tyszka, Zbigniew (Wydawnictwo Naukowe UAM, 2001)
The developed countries are entering the postindustrial epoch of the 21st century now. The automatozation will make its progress and next to it the a cyborgization” o f production and services, connected with scientific and technological development, especially in the field of most modern branches of technology (electronics, computing industry, modern medicine, and the development of contemporary media leading to the virtualization). Constantly growing exchange of information, the medialization of modern societies, the interweaving of real world with virtual one - all of this are the factors which will change the existence of families and individuals. We may expect futher progress of socjal atomization and the loosening of links within nuclear family and extended family. Divorces will be coming to life even more frequently, and the number of informal relationships (provided, from the sociological point of view, with family-like traits) will grow, as well as the number of incomplete families (without mother or father) and the number of individuals not sharing their living space with anyone. The basic need which supports the survival of family will be yearning for having close human relation with someone else.
A man and family in XXI century. A time of hope or the civilization of terment?